AN ANALYSIS OF BPJS PATIENTS' SATISFACTION INDICATORS IN INPATIENT ROOM IN THE WALED REGIONAL GENERAL HOSPITAL - Depi Yulyanti; Sintya Devi; wahyudin wahyudin (Insights in Public Health Journal, 2020)
Background : Patient satisfaction is a major problem that occurs in hospitals. Waled allegedly complained about the hospital concerning concern in providing services to BPJS patients, and there were differences in BPJS patient visits in inpatient services in 2014 to 2015 as many as 720 patients, then sought an increase Back in 2016 as many as 255 patients. However, this increase was not significant at the time of the decline in 2015. Aims: This study analyzes the indicators of BPJS patient satisfaction in the inpatient services of the Waled Hospital in 2018. Methods: This type of research was quantitative with descriptive research methods. The research population was 178, obtained as many as 123 samples, sampling using purposive sampling technique. Data analysis used univariate analysis. Results: The results of the study were 84.85% of patients satisfied with the service, as many as 78.8% of patients were satisfied with the doctor's service, as much as 78.2% of patients were satisfied with the care of nurses, as many as 94.3% of patients were satisfied with the patient's meal service, as many as 86 0% of patients were satisfied with medical facilities, as many as 85.9% of patients were satisfied with medication services, as many as 60.6% of patients were satisfied with the condition of hospital facilities, as many as 47.0% of patients were satisfied with the condition of the treatment room facilities, as many as 97 0% of patients are satisfied with outgoing administration services. Conclusion: Hospitals can find out indicators of patient satisfaction that are still low, it is recommended that the hospital should make SPO complaints about damaged facilities so that the hospital knows and immediately fixes it. So that patient satisfaction can continue to increase.